1999
DOI: 10.1161/01.cir.99.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet, Traditional Risk Factors, and the Rate of Cardiovascular Complications After Myocardial Infarction

Abstract: The protective effect of the Mediterranean dietary pattern was maintained up to 4 years after the first infarction, confirming previous intermediate analyses. Major traditional risk factors, such as high blood cholesterol and blood pressure, were shown to be independent and joint predictors of recurrence, indicating that the Mediterranean dietary pattern did not alter, at least qualitatively, the usual relationships between major risk factors and recurrence. Thus, a comprehensive strategy to decrease cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
1,488
5
115

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,602 publications
(1,662 citation statements)
references
References 30 publications
54
1,488
5
115
Order By: Relevance
“…Our findings are consistent with the potential role of wine consumption as one of the beneficial elements of a Mediterranean-style diet, 39,40 but further corroboration is still needed and may come from large follow-up studies conducted in Mediterranean populations.…”
Section: Resultssupporting
confidence: 88%
“…Our findings are consistent with the potential role of wine consumption as one of the beneficial elements of a Mediterranean-style diet, 39,40 but further corroboration is still needed and may come from large follow-up studies conducted in Mediterranean populations.…”
Section: Resultssupporting
confidence: 88%
“…Two clinical studies have examined the effects of ALA on hard CVD end points, the Lyon Diet Heart study28 and the Alpha‐Omega trial,29 both conducted in myocardial infarction survivors. A large benefit in reduction of reinfarction in the Lyon study could not be ascribed entirely to ALA, as other dietary changes took place,28 whereas the Alpha‐Omega trial revealed a trend toward CVD protection for ALA in patients receiving up‐to‐date cardiologic treatment 29. There have been no primary prevention trials with ALA, only observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Populations consuming a diet rich in vegetables, olive oil, fish and wine (Mediterranean diet, MD) had the lowest mortality among the seven countries included in that study. The benefits of this diet can apparently be transferred to populations of other ethnic origins (Kouris-Blazos et al, 1999) and have also been reproduced in secondary prevention trials (de Lorgeril et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…However, despite reports indicating that light-to-moderate alcohol consumption reduces both CV mortality (Thun et al, 1997) and the risk of stroke (Berger et al, 1999), wine drinking also has been related to the intake of healthier diets (Tjonneland et al, 1999) and other advantageous lifestyle characteristics (Wannamethee & Shaper, 1999), to which CV benefits are attributed. Thus, the health benefits of phenolic acids and polyphenols contained in red wine may be indiscernible in populations that ingest large amounts of fruit and vegetables, whereas these benefits could be distinctly apparent in populations with relatively low intakes of these kinds of foods (de Lorgeril et al, 1999). In this regard, the proposal that wine is a major determinant of the benefits derived from MD (Renaud & de Lorgeril, 1992) still needs to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%